Interview with Patrick Sutton and Brian Maguire - Andrade, Fábio Souza; Ramos, Luiz Fernando (ABEI Journal, 2015)
This interview took place on 15th September 2015, at the Universityof São Paulo, when the Director Patrick Sutton and the painter and actor Brian Maguire arrived from Rio de Janeiro where Beckett’s play Waiting for Godot was performed.Keywords: Patrick Sutton; Brian Maguire; Waiting for godot.